High efficient internal combustion engine using partially premixed combustion with multiple injections. (1st January 2019) - Yin, Lianhao; Lundgren, Marcus; Wang, Zhenkan; Stamatoglou, Panagiota; Richter, Mattias; Andersson, Öivind; Tunestål, Per
Highlights: Partially premixed combustion was realized with single, double, and triple injections under different EGR. Single double and triple injections were compared both on metal and optical engine. The in-cylinder fuel movement as a function of crank angle was evaluated within a cycle using a high-speed camera. The efficiency of single, double, and triple injections were evaluated. Abstract: Improving the efficiency of the powertrain system is of great importance to reduce the greenhouse gas CO2 . Advanced combustion engine with Partially Premixed Combustion (PPC) is one of the best solutions. It is proved to have a high engine efficiency and low emission level. Using multiple injections is a good way to achieve PPC. The efficiencies using multiple injections were evaluated on a metal engine with modern architecture and the reasoning behind that was explored on an optical engine. The metal engine results shown that the point with optimized multiple injections is of higher efficiency than a single injection. Optical results demonstrated that the direct interaction of the first and later injection, as well as the interactions of the fuel and the in-cylinder bulk flow fields and surfaces, could affect mixing and fuel movement and, hence the efficiency. One of the reasons why the optimized multiple injections have a higher efficiency is that the center of the fuel is moved close to the center of the cylinder. Thus, the heat transfer between the heat produced from the fuel-gas mixture and the cylinder liner can be reduced by the isolation. This explains how the injections influence the fuel distribution and the heat transfer and, hence, the engine efficiency.